Oil spill, an ecological disaster literature review on its impact on health - Ordóñez, Carol (2022)
Petroleum consists mainly of hydrocarbons and metals, in varying concentrations. It is highly flammable and throughout history has been used as a fuel and energy source. Oil spills are disasters that alter different ecological levels and affect different sectors, mainly the environment, health, the economy and tourism. Several studies have shown both short and long-term effects on human health, especially at the reproductive, cardio-respiratory, hepatic, hepatic, renal, metabolic and mental levels. Exposure occurs by ingestion, absorption through intact skin and inhalation. In Peru, on 15 January 2022, an oil spill in Ventanilla, Callao, of about 12,000 barrels of oil generated harmful effects on marine and ornithological species and on the quality of life of artisanal fishermen. Its impact is still under evaluation due to the slow response of those responsible for slowing down the advance of the spill in the area, which has extended 34.4 km to the Chancay area. For this reason, the present review details the international scientific evidence on the effects, mainly on health, that an oil spill can have. The findings reported in the literature contribute to broaden the knowledge on the long- term effects of oil spills on health, considering the need for longitudinal studies on species and populations close to the areas directly affected by these ecological disasters.